AN ANALYSIS DIGITAL READING CHALLENGES AND STRATEGIES : STATE JUNIOR HIGH SCHOOL SMPN 3 PATTALLASSANG - Hartati, Sri; Syam, Ummi Khaerati; Hijrah (Journal of Computer Interaction in Education, 2022)
The purpose of this study is to determine what challenges students face when reading digitally and what strategies students use when reading digitally in eighth grade one at SMPN 3 Pattallassang. This was a qualitative descriptive research method. Data for the study was gathered through direct observation and questionnaires administered in schools. The participants in this study were eighth-grade students at SMPN 3 Pattallassang. A questionnaire was used to collect samples. Based on the research, it was found that the challenges and strategies of students in answering the questionnaire were underlining reading that was not understood, lack of words, inadequate quality of internet access, poor learning environment, use of smartphones from both parents, finding out the description of the material to be read, becoming an active thinker, namely finding the intent or composition, trying to write important words or sentences in the reading, writing a summary of what was read, reading first after reading the reading material. digital and five strategies that students lack exemplary in digital reading.